GLOVE: The Global Plastic Ingestion Initiative for a cleaner world. (December 2022) - Monteiro, Raqueline; Andrades, Ryan; Noleto-Filho, Eurico; Pegado, Tamyris; Morais, Leonardo; Gonçalves, Myckey; Santos, Robson; Sbrana, Alice; Franceschini, Simone; Soares, Marcelo O.; Russo, Tommaso; Giarrizzo, Tommaso
Abstract: Plastics are one of the most used materials in the world. Their indiscriminate use and inappropriate disposal have led to inevitable impacts, for instance ingestion, on the environment arousing the attention of the global community. In addition, plastic ingestion studies are often written in scientific jargon or hidden behind paywalls, which makes these studies inaccessible. GLOVE is an online and open-access dashboard database available at gloveinitiative.shinyapps.io/Glove/ to support scientists, decision-makers, and society with information collected from plastic ingestion studies. The platform was created in the R environment, with a web interface developed through Shiny. It already comprises 530 studies, including all biological groups, with 245, 366 individual records of 1458 species found in marine, freshwater, and terrestrial environments. The main goal of the GLOVE dashboard database is to improve data accessibility by being a scientifically useful grounded tool for designing effective and innovative actions in the current scenario of upcoming global and local agreements and actions on plastic pollution. Graphical abstract: Unlabelled Image Highlights: Plastic pollution causes harmful effects from individual to ecosystem-level. GLOVE is an open-access dashboard database focused on ingested plastic debris by wild animals. The platform supports political and education science-based actions for multiple stakeholders. It includes 530 studies representing 1458 species from aquatic and terrestrial ecosystems.